COMPARING THE INFESTATION EFFECT BY LESSER GRAIN BORER (RHIZOPERTHA DOMINICA) ON 10 WHEAT VARIETIES BEFORE AND AFTER THRESHING - O .S .Mohammad (Mesopotamia Journal of Agriculture)
This study was conducted to test the ability of the lesser grain borer to attack 10 varieties of wheat and caused any injury to the grain stored in their ears, and to compare that with the infestation of the released seeds of the same varieties. The results showed that the beetle failed to cause any damage to the first group of wheat, although the process of re-infection were repeated three times, and that the incidence of the insect for all varieties of wheat stored in the ears was zero % , and that all insects were dead within a maximum of 10 days after putting them on the ears, while the percentage of germination of the stored grains reached 75.2% as an average.,while it was decreased for with an average of 32.3 %. It also resulted in injury insect to a significant decrease and clear the proportion of gluten in the flour of infected seeds with an average of 19.9 % as compared with that stored in the ears showing an average of 35.2% . On the other hand the percentage of infection for the released seeds reached 52.3 % as an average., as confirmed by the amylograph test the existence of significant differences between the values of the maximum viscosity were very high in the infected samples giving an average of 901 B.U while it was in the sound 548.4 B.U.,such differences for some of the sensory qualities of grain exposed to insect injury made it unacceptable from the standpoint of work manufacturing laboratory bread or some other pastry.